(untitled) (Journal of Hama University, 2026)
Summary: The current research aims to determine the skills of interconnected thinking included in the content of the science book for the sixth grade, and to know the degree of the availability of these skills in it, the researcher used the descriptive analytical curriculum, the research sample included the content of the science curriculum for the sixth grade of the second semester of the second semester of the academic year 2024-2025 The research tools consisted of a content analysis tool that included the list of interconnected thinking skills, by ((33 skills A subtitle distributed over three main skills: “Determining the ideas to be linked, strengthening the links between ideas, determining the result to be reached. _ The bonding thinking skills are available in a moderate degree. Availability of applied and procedural activities to develop thinking, connection and conclusion skills. - The results of the analysis showed that the most frequent interconnected thinking skills are the skill of "strengthening ties between ideas" by 35.19%, followed by the second place skill determining the result to be reached "by 33.5%, and in the third place the skill" determining the ideas to be linked "by 31.28% . - The results showed distribution care depending on the main skills, as well as according to the components of the main skill from sub -skills, as well as according to the arrangement of these skills in the activities of the book despite their indirect receipt, and in light of the results the researcher recommended that the main and subsidiary skills distribute activities to use the activities of the interconnected thinking skills in content Science book is direct examples that include interconnected thinking skills.